The History of Munawatul Khair Arabic School Lampung Between 1930-1950 - Seli Anjani; Ahmad Basyori; Aan Budianto; Abd Rahman Hamid; Agus Mahfudin Setiawan (Tarikhuna: Journal of History and History Education, 2024)
Munawatul Khair Arabic School is one of the madrasah that played pivotal role in the history of Islamic education in Lampung during 1930-1950. This madrasah began in Tanjung Agugn, Bengkulu in 1925, founded by K.H. Hosen bin Abd Syukur. The madrasah is centered in Tanjung Karang, Bandar Lampung in 1930. This study is a form of literature research using historical and philosophical approach. The data source was collected from primary and secondary data. Primary data of this study is based on the records of the madrasah. While secondary data was similar researches from other researchers. This research used historical method, (1) Heuristic: data collection from primary and secondary data, (2) Criticism source, related criticism given internally or externally, (3) Interpretation involves combining various data sources to interpret a study, (4) Historiography, the historian’s endeavor to reconstruct a history by writing it into a research.The result of this study aims to enrich the value of education history, especially Islamic education in Lampung, focusing on the significant role of Madrasah Munawatul Khair Arabic School as a leading institutionof its time. Little history is yet to be discovered regarding education in Lampung, specifically detailing the development of education in Lampung. The establishment of Munawatul Khair Arabic School in Lampung and Bengkulu provided Islamic education for the indigenous people of Indonesia. This action was particularly significant given the limited access to Islamic education during the colonial and post-colonial eras. While little impact this madrasah had provided globally, its influence was felt locally, especially among marginalized communities who had limited access to government-run schools during that period.